Sistema de gestão da qualidade para Centros de Coleta e Processamento de Sêmen bovino: elaboração, implantação e impacto - Goularte, Karina Lemos (2014)
Although more than 12 million doses of bull frozen semen were sold in Brazil in 2012, the production process of the doses sold by the artificial insemination centers registered in the Ministry of Agriculture, Livestock and Supply is not yet standardized. The hypothesis of the present study is that the design and implementation of a hazard analysis and critical control points (HACCP) system in a bull artificial insemination center can identify steps potentially harmful to the viability of semen doses, to decrease their rejection and to improvement their final quality, after the adoption of preventive and process control measures. The implementation of the HACCP system identified hazardous steps for the quality of the produced semen doses, leading to a reduction in their contamination during processing (P<0.05). There was also an increase in progressive motility and plasma membrane and acrosome integrity of spermatozoa (P<0.05) after implementing the HACCP system, which resulted in reduced rejection of semen batches and doses (P<0.05) and decreased production costs. Thus, the execution of the HACCP system standardized the production process of bull frozen semen, with improved sperm quality and reduction in both rejection of doses and costs to the industry. Additionally, during the sandwich doctorate program at the University of Calgary (Canada), the involvement of angiotensin converting enzyme in the capacitation process and in vitro fertilization in cattle was evaluated. After blocking the enzyme s activity by the specific inhibitor captopril, there were similar levels of tyrosine phosphorylation and cleavage and embryonic development until the blastocyst stage in comparison with the control group (P>0.05). Therefore, the present study suggests that the angiotensin converting enzyme is neither required for sperm capacitation nor involved in in vitro fertilization in cattle.